Boosting innovation in the water sector - The role and lessons learned from collaborative projects - Alegre, H. (2015)
A key worldwide challenge in most sectors is to boost the effective adoption of innovation, as underpinned by the new European Union research programme Horizon 2020, which focuses on increasing innovation in Europe from 2014 to 2020. This is particularly relevant in the water sector, often perceived as conservative and averse to change. This paper discusses the role that collaborative knowledge-transfer projects can play in effectively rolling out R&D in the water industry. LNEC (Laboratório Nacional de Engenharia Civil) has designed a structured model based on a phased programme and a network of utilities and researchers. The paper presents the core principles, the rationale, the model and methods used, and the theoretical background, as well as the project’s impact, outcomes and products. The discussion highlights the lessons learnt and provides a formal analysis of the advantages of focusing on middle management as an effective entry point, even if innovation is needed across the organization. Making training materials, guidelines, use cases, data and software publicly available after the project’s end has proven to have a decisive multiplying effect. The paper also argues in favour of the collaborative model as a basis for R&D sustainability, and details on-going and planned developments.